2013
DOI: 10.1016/j.juro.2012.11.049
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the 5-HT 2A/2C Receptor Agonist DOI on Micturition in Rats with Chronic Spinal Cord Injury

Abstract: High frequency oscillation seems to reflect external urethral sphincter burst activity during voiding. Bladder voiding efficiency and high frequency oscillation activity were decreased in spinal cord injured rats. High frequency oscillation activity can be enhanced by 5-HT2A receptor agonism, improving voiding efficiency. To our knowledge it remains to be studied whether these results may have implications for the future treatment of voiding dysfunction in patients with spinal cord injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 28 publications
1
15
1
Order By: Relevance
“… proposed that the L3–L4 spinal segment may have a specific role in mediating EUS bursting activity and regulating the pelvic‐EUS reflex arc in normal rats. The DOI‐evoked facilitation of EUS bursting activity also occured in rats after chronic transection of the spinal cord at the mid‐thoracic level, which is clearly dependent on activation of 5‐HT2A receptors in the lumbosacral spinal cord .…”
Section: Discussionmentioning
confidence: 86%
“… proposed that the L3–L4 spinal segment may have a specific role in mediating EUS bursting activity and regulating the pelvic‐EUS reflex arc in normal rats. The DOI‐evoked facilitation of EUS bursting activity also occured in rats after chronic transection of the spinal cord at the mid‐thoracic level, which is clearly dependent on activation of 5‐HT2A receptors in the lumbosacral spinal cord .…”
Section: Discussionmentioning
confidence: 86%
“…The detailed cystometric method has been described previously . After the urinary bladder was exposed by a midline abdominal incision, a catheter (PE‐50 Smiths Medical) was inserted through the top of the bladder to measure the intravesical pressure (IVP) of the bladder.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, the involvement of the 5‐HT 2A receptor in spinal micturition control was demonstrated in urethane‐anaesthetized chronic spinal cord injured rats, in which i.v. administration of the 5‐HT 2A/2C receptor agonist 2,5‐methoxy‐4‐iodoamphetamine (DOI), stimulated high frequency oscillations (HFOs) and micturition ; however, the molecular mechanisms that lead to these observed changes remain poorly understood. We tried to clarify this by using i.t.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, distinct subtypes of 5‐HT receptors were characterized not only in supraspinal sites but also in the spinal cord, indicating central 5‐HT mechanisms involved at multiple levels in the nervous system. Previous studies showed that, in the rat spinal cord, stimulating 5‐HT 1A receptors had an excitatory physiological role in the control of bladder function whereas activation of 5‐HT 2A receptors inhibited the reflex . Thus, serotonin is an important contributor to the modulation of LUT function along with other neurotransmitters.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that, in the rat spinal cord, stimulating 5-HT 1A receptors had an excitatory physiological role in the control of bladder function whereas activation of 5-HT 2A receptors inhibited the reflex. 7,8 Thus, serotonin is an important contributor to the modulation of LUT function along with other neurotransmitters.…”
mentioning
confidence: 99%